National Security of Sri Lanka: Importance of Mass Media and Communication - Senaratne, B. (Faculty of Graduate Studies , University of Sri Jayewardenepura, 2017)
This decade is proving to be crucial to national security of Sri Lanka as there are many international pressures upon the country. Some of these pressures are legal whilst others are economic. However, the common nature of all these pressures is that it threatens Sri Lanka’s national security and obstructs the development of the country. Therefore it is imperative that Sri Lanka conducts itself in a manner that safeguards the country’s national security. In this context, this research highlights the importance played by mass media and communication in safeguarding Sri Lanka’s national security and interests. The research thus provides an analysis of mass media in reporting international pressures on Sri Lanka. It will also analyse the media relations of the Ministry of Foreign Affairs against these international pressures. Towards this end, the research mainly utilises secondary data such as newspaper articles, press releases, feature articles from reputed websites and reports from social media etc. The research will also analyse media relations against existing communication models among others Shannon – Weaver and Defleur and identify a mechanism that will help safeguard Sri Lanka’s image. The research identified there is a communication gap and that mass media is not being utilised appropriately by the relevant authorities in presenting and projecting the image of Sri Lanka. In conclusion, the research provides a communication tool for the Ministry of Foreign Affairs to follow when interacting with the media both local and international in order to safeguard Sri Lanka’s national security. It also highlights the importance of social media and its uses in the future and finally provides a link to the interconnectedness of national security and mass media as they both together assist with the development of the country
Keywords: Foreign affairs, national security, mass media and communication